Impact of diabetes status on immunogenicity of trivalent inactivated influenza vaccine in older adults. Issue 3 (3rd December 2021) - Spencer, Sarah; Chung, Jessie R.; Belongia, Edward A.; Sundaram, Maria; Meece, Jennifer; Coleman, Laura A.; Zimmerman, Richard K.; Nowalk, Mary Patricia; Moehling Geffel, Krissy; Ross, Ted; Carter, Chalise E.; Shay, David; et al.
Abstract: Individuals with type 2 diabetes mellitus experience high rates of influenza virus infection and complications. We compared the magnitude and duration of serologic response to trivalent influenza vaccine in adults aged 50–80 with and without type 2 diabetes mellitus. Serologic response to influenza vaccination was similar in both groups: greater fold‐increases in antibody titer occurred among participants with lower pre‐vaccination antibody titers. Waning of antibody titers was not influenced by diabetes status.